2018
DOI: 10.1007/s13197-018-3533-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of multigrain premix on nutritional, in-vitro and in-vivo protein digestibility of multigrain biscuit

Abstract: Effect of addition of multigrain premix (MGP) prepared using a combination of cereals, pulses and oilseeds at 40% level, on nutritional properties of multigrain biscuit, its in-vitro and in-vivo protein digestibility and protein profiling were studied. The incorporation of MGP significantly increased the protein content (from 7.37 to 16.61%), insoluble dietary fiber (from 1.71 to 6.67%), soluble dietary fiber (from 0.46 to 2.42%). The significant increase in the levels of isoleucine (ND-34.79%), methionine (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
(38 reference statements)
2
8
0
Order By: Relevance
“…Substitution of wheat flour with rice flour has increased protein digestibility in biscuits [74]. Furthermore, in terms of improving the nutritional profile of baked products, diversification in the used cereals can come up to the suboptimal amino acid composition of wheat [75,76].…”
Section: Protein Digestibilitymentioning
confidence: 99%
“…Substitution of wheat flour with rice flour has increased protein digestibility in biscuits [74]. Furthermore, in terms of improving the nutritional profile of baked products, diversification in the used cereals can come up to the suboptimal amino acid composition of wheat [75,76].…”
Section: Protein Digestibilitymentioning
confidence: 99%
“…Mushrooms are rich in fibre and adding powdered mushrooms may improve protein hydrolysis via the effects of fibre on the physical structure of the biscuit. Ashwath Kumar, et al [45] discovered that fibre enriched wheat biscuits (TDF, 9.09%) had a higher rate of protein hydrolysis. Sciarini, et al [46] found that the addition of oat bran fibre and resistant starch into a gluten-free bread (rice flour) increased the percentage of protein hydrolysis and suggested that this was achieved by disrupting the crumb structure.…”
Section: Protein Profile and Soluble Protein Content After Digestionmentioning
confidence: 99%
“…A similar intense band of high molecular weight was observed by Wang et al 40 in stored buckwheat grains. Contrarily, in a study conducted by Kumar et al 14 more intense protein bands were found near 6.5 kDa and between 29 and 40 kDa in barley. Black rice showed one band near 100 kDa, which might be the specific protein band related to rice pericarp colour.…”
Section: Resultsmentioning
confidence: 78%
“…SDS-PAGE analysis. The method described by Kumar et al 14 was used to conduct the SDS PAGE analysis of the various selected grains viz. hull-less barley, buckwheat, and black rice, with minor modication.…”
Section: Physical Morphometric and Structure Analysismentioning
confidence: 99%